Guidelines for Public Expenditure Management. (International Monetary Fund, 1999)
Traditionally, economics training in public finances has focused more on tax than public expenditure issues, and within expenditure, more on policy considerations than the more mundane matters of public expenditure management. For many years, the IMF's Public Expenditure Management Division has answered specific questions raised by fiscal economists on such missions. Based on this experience, these guidelines arose from the need to provide a general overview of the principles and practices observed in three key aspects of public expenditure management: budget preparation, budget execution, and cash planning. For each aspect of public expenditure management, the guidelines identify separately the differing practices in four groups of countries - the francophone systems, the Commonwealth systems, Latin America, and those in the transition economies. Edited by Barry H. Potter and Jack Diamond, this publication is intended for a general fiscal, or a general budget, advisor interested in the macroeconomic dimension of public expenditure management.